Antimutagenic effects of the mushroom Agaricus blazei Murrill extracts on V79 cells - Menoli, RCRN; Mantovani, M. S.; Ribeiro, Lúcia Regina [UNESP]; Speit, G.; Jordao, B. Q. (Elsevier B.V., 2001)
Agaricus blazei Murrill, a native mushroom in Brazil, has been widely consumed in different parts of the world due to its medicinal power. Its anticarcinogenic activity has been shown in experimental animals, and antimutagenic activity has been demonstrated only in Salmonella. In this work, the multagenic and antimutagenic activities of mushroom teas of strains AB96/07, AB96/09 and AB97/11 were evaluated in Chinese hamster V79 cells, using the comet assay and the micronucleus test. The cells were treated with three different concentrations (0.05, 0.1 and 0.15) of teas prepared from a 2.5% aqueous solution, under three different temperatures: (1) room (20-25 degreesC); (2) ice-cold (2-8 degreesC); and (3) warm (60 degreesC). The teas were applied in co-, pre- and post-treatments in combination with the mutagen methyl methanesulfonate (MMS; 1.6 x 10(-4) and 4 x 10(-4) M). The duration of the treatment was 1 h in the comet assay and 2 h in the micronucleus test. The results showed that the mushroom was not mutagenic itself. Nevertheless, the mushroom is an efficient antimutagen against the induction of micronuclei by MMS in all concentrations and preparations tested. The observed reductions in the frequencies of micronuclei ranged from 61.5 (room temperature 0.1% tea in post-treatment) to 110.3% (co-treatment with warm and ice-cold 0.15% tea). In the comet assay, the antimutagenic activity was detected only when the cells were pre-treated with the following teas: warm 0.1 and 0.15%, room temperature 0.05% and ice-cold 0.1%. The results indicate that the mushroom A. blazei extracts are antimutagenic when tested in V79 cells. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: Agaricus blazei Murrill; antimutagenesis; micronucleus test; comet assay; V79 cells; methyl methanesulfonate